Analysis of Transfer Pricing Practices in Avoiding Tax Payments in Indonesia - Gultom, Irfan Marganda; Wardhani, Nurhastuty Kesumo (Manunggal Halim Jaya, 2025)
This study aims to analyze the transfer pricing practices by PT. XX in efforts to avoid tax payments in Indonesia and to identify the methods used to reduce tax burdens through profit shifting. The approach used is a qualitative method with a case study on PT. XX, supported by a review of literature and tax regulations, including the Minister of Finance Regulation No. 22/PMK.03/2020. Data were obtained from interviews with PT—XX employees, as well as an analysis of two contracts and relevant types of internal transactions. The results show that PT. XX's transfer pricing practices include strategies such as profit shifting, charging unreasonably high costs, and utilizing jurisdictions with lower tax rates. Regulatory gaps, the complexity of cross-border transactions, and weak supervision are factors driving these practices. Case studies of other companies, such as PT Adaro Energy Tbk, PT Toyota Motor Manufacturing Indonesia, and PT Toba Pulp Lestari, confirm the significant impact of these practices on the country's tax revenue. The study recommends strengthening regulations, enhancing the capacity of tax supervisory authorities, and harmonizing international standards related to transfer pricing. Additionally, companies are advised to implement Good Corporate Governance principles, and the government should improve its monitoring systems for affiliate transactions to reduce the risk of tax avoidance, particularly for specific products or services of PT. XX makes comparisons with other companies difficult, underscoring the need for further research on this issue.